2020
DOI: 10.1097/iae.0000000000002535
|View full text |Cite
|
Sign up to set email alerts
|

Blood Chromium-Cobalt Levels in Patients After Total Knee Arthroplasty and Their Effect on the Retinal Nerve Fiber Layer and Macular Ganglion Cell Complex

Abstract: Purpose: To study blood cobalt (Co) and chromium (Cr) levels in patients who have undergone total knee arthroplasty and their effect on the retinal nerve fiber layer and macular ganglion cell complex. Methods: One hundred patients who had undergone total knee arthroplasty and 50 healthy individuals who had no implants were included in the study. The patients were separated into two groups based on how long ago the prosthesis had been implanted (Group 1:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
15
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 29 publications
2
15
0
Order By: Relevance
“…There was no significant difference in anemic rate before surgery, and only one patient in the periarticular cocktail injection group received blood transfusion after surgery; also, the rates of wound infection and DVT were not increased in the subperiosteal cocktail injection group, which meant that this technique could reduce blood loss without increasing complications [33,34]. Otherwise, the reduced blood loss would also be helpful to decrease the prosthesis loosening rate [35][36][37].…”
Section: Discussionmentioning
confidence: 99%
“…There was no significant difference in anemic rate before surgery, and only one patient in the periarticular cocktail injection group received blood transfusion after surgery; also, the rates of wound infection and DVT were not increased in the subperiosteal cocktail injection group, which meant that this technique could reduce blood loss without increasing complications [33,34]. Otherwise, the reduced blood loss would also be helpful to decrease the prosthesis loosening rate [35][36][37].…”
Section: Discussionmentioning
confidence: 99%
“…Inadequately, previously reported staged operations have completed a large amount of osteotomy during the first stage of surgery, which is not conducive to the preservation of bone mass, and if the spacer is left in the body for a long period of time, there is a risk of its loosening or fragmentation, followed by the abrasion of bone mass. Studies have shown that long intervals can cause biofilm formation on the surface of the spacer and further cause continuous infection or reinfection [23][24][25][26]. Therefore, this study proposes the optimization with antibiotic cement beads and tibial plateau spacers.…”
Section: Discussionmentioning
confidence: 99%
“…Considerable levels of metal ions are released during cyclic wear simulation [20]. Clinically, this leads to elevated metal ion levels in the patient's blood [21][22][23]. In addition, the released metal ions accumulate in tissue surrounding the joint, and can lead to adverse local tissue reactions like metallosis [19,24].…”
Section: Discussionmentioning
confidence: 99%